2012
DOI: 10.1016/j.ijnt.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Missile injuries of spine and spinal cord in civilian Kashmir – Analysis and outcome evaluated by new Modified SKIMS-Functional Scales

Abstract: Spinal missile injuriesModified SKIMS-Functional Classification Modified SKIMS-Functional Outcome scale a b s t r a c t Aims: Since the emergence of missile injuries of spinal cord is a major managementchallenge due to its vulnerable vascularity, narrowly-packed neurons and tracts, associated injuries caused by kinetic-energy of missiles, we sought analysis and evaluation of missile injuries of spinal cord with the application of indigenously devised Modified SKIMSFunctional Classification, SKIMS-injury types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The dorso-lumbar junction (D12-L1) and lumbar 2 nd and 3 rd bodies were approached through Modified posterolateral Extra-pleural Retro-peritoneal approach. (17) In our study we found that the initial neurological deficit was the most important factor for the outcome of these patients, patients with incomplete injury at admission had good recovery and patients with complete injury at admission had poor outcome.…”
Section: Original Articlementioning
confidence: 50%
“…The dorso-lumbar junction (D12-L1) and lumbar 2 nd and 3 rd bodies were approached through Modified posterolateral Extra-pleural Retro-peritoneal approach. (17) In our study we found that the initial neurological deficit was the most important factor for the outcome of these patients, patients with incomplete injury at admission had good recovery and patients with complete injury at admission had poor outcome.…”
Section: Original Articlementioning
confidence: 50%
“…18 The present study reveals that all types of approaches and procedures were used in 79.01% (527/667) patients to decompress spinal cord and roots, while simultaneously to construct and stabilize the spinal column. 19 Silberstein and Rabinovich reported a mortality of 16.8% and most of the patients who died (84.8%) had injuries to the cervical spinal cord at the level of C4 and above. 20 The present walnut-spine study showed that ASIA neurologic grade of A and B on admission in more than 94% cervical injuries and in more than 86% of dorsal spinal injuries caused by walnut-tree falls had worst outcome in terms of severe disabilities and deaths.…”
Section: Discussionmentioning
confidence: 99%